Konsep Penahanan dalam Sistem Hukum Indonesia - Al Farizi, Dizar (University of Jember, 2016)
Detention is one of the forced efforts to enforce the law known in the criminal justice system, also, to arrest, search, confiscation, and wiretapping. The absolute authority possessed by law enforcement officials to detain a person suspected of committing a criminal act with the threat of a certain penalty makes detention very easy. Even though detention can be carried out, it must be carried out solely to examine the criminal case itself. Detention itself is an addition to an examination of a criminal case. The detention